Employee Well-Being di Era Digital Workplace: Tinjauan Literatur Sistematis tentang Kesehatan, Keterikatan, dan Produktivitas Pegawai - Muhamad Nukha Murtadlo; Iva Sofi Gunawati; Inarotul Caturmufidarini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Digital transformation has driven significant changes in organizational work environments through the adoption of various digital technologies that support communication, collaboration, and flexible work practices. This transformation has led to the emergence of the digital workplace concept, which presents both opportunities and challenges for employee well-being. This study aims to systematically review previous research findings on employee well-being in digital workplaces and identify their implications for organizational performance and productivity. The study employed a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. The literature search was conducted using various scholarly sources relevant to employee well-being, digital workplace, technostress, employee engagement, and work-life balance. Articles meeting the inclusion criteria were analyzed using a thematic analysis approach to identify the major themes emerging from the existing literature. The findings indicate that the success of digital transformation depends not only on technology adoption but also on an organization's ability to maintain and enhance employee well-being. Digital workplaces can improve flexibility, collaboration, and work efficiency; however, they may also create challenges such as technostress, digital fatigue, and blurred boundaries between work and personal life. Therefore, organizations should adopt a human-centered approach to create productive, healthy, and sustainable digital work environments that support both employee well-being and organizational outcomes.